2016
DOI: 10.1039/c6nr03655d
|View full text |Cite
|
Sign up to set email alerts
|

Electron and phonon properties and gas storage in carbon honeycombs

Abstract: A new kind of three-dimensional carbon allotropes, termed carbon honeycomb (CHC), has recently been synthesized [PRL 116, 055501 (2016)]. Based on the experimental results, a family of graphene networks are constructed, and their electronic and phonon properties are studied by various theoretical approaches. All networks are porous metal with two types of electron transport channels along the honeycomb axis and they are isolated from each other: one type of channels is originated from the orbital interactions … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 59 publications
0
46
0
1
Order By: Relevance
“…According to the theoretical calculations or MD simulations, the carbon honeycomb exhibits anisotropic thermal transport properties, i.e., a larger axial thermal conductivity than the transverse thermal conductivity. These in silico studies have also shown marked influences on the thermal conductivity of the honeycomb structures from various factors, such as the cell structures (or morphologies),141,142c mechanical strain,142b and temperature 142a. Figure b illustrates the specific axial and lateral thermal conductivity of a carbon honeycomb structure with varying density as obtained from density functional theory (DFT) calculations.…”
Section: D Nanostructures For High Thermal Conductivitymentioning
confidence: 97%
“…According to the theoretical calculations or MD simulations, the carbon honeycomb exhibits anisotropic thermal transport properties, i.e., a larger axial thermal conductivity than the transverse thermal conductivity. These in silico studies have also shown marked influences on the thermal conductivity of the honeycomb structures from various factors, such as the cell structures (or morphologies),141,142c mechanical strain,142b and temperature 142a. Figure b illustrates the specific axial and lateral thermal conductivity of a carbon honeycomb structure with varying density as obtained from density functional theory (DFT) calculations.…”
Section: D Nanostructures For High Thermal Conductivitymentioning
confidence: 97%
“…The atomic positions were optimized using the conjugate gradient method. The energy and force convergence criteria are set to be 10 -6 eV and only 0.18 eV/atom smaller than diamond but greater than some other carbon allotropes such as CKL [53] and CHC-2 [54]. [Detail structure parameters can be seen in Table S1 in Supplementary Information (SI)].…”
Section: Realization Of Interlocking Nodal Chains In Carbon Networkmentioning
confidence: 99%
“…While scaling 2D graphene up to its three-dimensional counterparts there are many significant challenges in maintaining the nature and intrinsic properties of individual graphene sheets in the resulting three-dimensional bulk structures. But the comprehensive theoretical studies of CHs [9,[16][17][18][19][20][21][22][23] proved their superb strength and stability. This strength remains at a high level but tunable with different cell sizes [17,24] and crucially depends on defectness of CH structures [25].…”
Section: Theory Of Chs and Important Applicationsmentioning
confidence: 99%